2021
DOI: 10.1016/j.heliyon.2021.e08551
|View full text |Cite
|
Sign up to set email alerts
|

The development of internet financial reporting publications: A concise of bibliometric analysis

Abstract: This paper identifies the main areas and the development of the field of internet financial reporting publications and to suggest future research directions. Internet use for corporate financial reporting represents a voluntary approach to consolidate printed sustainability reports which have increasingly been published by large companies in recent years. Using a bibliometric analysis, this paper examined a sample of 246 studies from Web of Science, Scopus, Emerald, Springer, Proquest, Ebsco, and Science Direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…For example, in the study by Frias-Aceituno et al [ 68 ]; García-Sánchez, who was the third author, found that the board has a role in the dissemination of integrated corporate social reporting. This finding is consistent with other bibliometric analyses on board and CSR or sustainability reporting [ 20 ]. These findings imply that more studies are needed for a more comprehensive understanding of the relationship between BGD and CSR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, in the study by Frias-Aceituno et al [ 68 ]; García-Sánchez, who was the third author, found that the board has a role in the dissemination of integrated corporate social reporting. This finding is consistent with other bibliometric analyses on board and CSR or sustainability reporting [ 20 ]. These findings imply that more studies are needed for a more comprehensive understanding of the relationship between BGD and CSR.…”
Section: Discussionsupporting
confidence: 92%
“…It has recently become more popular in the discipline of Management (e.g. [ 20 , 21 , [41] , [42] , [43] , [44] ]). Moreover, it has also been employed to map CSR-related research [ 9 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colour of the node and line represent the year of the documents contained the keywords were published. A lighter colour of the node and line show the recent focus of keywords in Granger causality [ 137 ]. The recent research in Granger causality focused on renewable energy, non-renewable energy, trade openness, carbon emissions, ARDL, EKC, and globalization.…”
Section: Resultsmentioning
confidence: 99%
“…Bibliometric analysis is a method based on statistical data used to measure the impacts of parameters such as scientific publications, authors, institutions, scientists, and keywords (Biresselioglu et al, 2020). An analysis of publications related to a given research discipline is known as bibliometric analysis, and it is commonly used to assess knowledge structure and development in Natural Sciences, Social Sciences, and Humanities (Pauna et al, 2019;Xie et al, 2020;Katoch, 2021;Murdayanti and Khan, 2021;Mörschbächer and Granada, 2022).…”
Section: Methodsmentioning
confidence: 99%